PERFORMANCE OF THE LABORATORY WORK "OSCILLATIONS IN L-R-C SERIES CIRCUIT" BY USING МАТLAB SOFTWARE PACKAGE - Kabylbekov K.A; Abdrakhmanova Kh.K; Saidakhmetov P.A; Kedelbaev B.Sh; Issaev E.B (Academic Scientific Journal of Computer Science, 2019)
The article suggests the calculation and visualization of oscillations that occur in the L-R-C series circuit. It contains the formulation of the problem, the physical analog and mathematical model of the process and the Matlab software program codes describing the process. There are graphs of the current through the circuit versus time, of the voltage across the inductor and across the resistor versus time. Because of the resistance the electromagnetic energy in the circuit is dissipated and converted to internal energy of circuit materials. The article also contains the assignments for students’ individual work which require them to make comparative conclusions about various oscillations that occur when parameters of the circuit change.